Research progress and molecular mechanism of oridonin in the treatment of malignant melanoma - Deng, Tinghan; Wu, Jingping; Cheng, Hongbin; Lu, Jun (Frontiers in Oncology, 2025)
Malignant Melanoma (MM) is a highly invasive and easily metastasizing skin cancer. Although current treatments have made certain progress in targeted therapy and immunotherapy, drug resistance and side effects remain urgent problems to be addressed. Oridonin, an active diterpenoid compound derived from the traditional Chinese medicine herb Rabdosia rubescens, has garnered widespread attention in recent years for its multi-target anti-tumor effects. This review systematically summarizes the research progress of oridonin in the treatment of malignant melanoma, focusing on its multiple molecular mechanisms, including inhibition of tumor cell proliferation, induction of apoptosis, inhibition of invasion and metastasis, suppression of angiogenesis, and modulation of the immune microenvironment. Through in vitro cell experiments and in vivo animal model studies, oridonin has demonstrated significant anti-melanoma activity and has shown potential synergistic effects when used in combination with existing therapies. Additionally, the optimization of pharmacokinetics and toxicology of oridonin has laid a foundation for its clinical application. However, clinical trial data on oridonin are still limited, and future high-quality clinical studies are needed to verify its safety and efficacy. As a natural product with multiple anti-tumor mechanisms, oridonin exhibits broad prospects as a potential therapeutic agent for malignant melanoma, but further basic and clinical research is required to promote its clinical translation.